2019
DOI: 10.3390/jcm9010010
|View full text |Cite
|
Sign up to set email alerts
|

HCMV Infection in a Mesenchymal Stem Cell Niche: Differential Impact on the Development of NK Cells versus ILC3

Abstract: Human cytomegalovirus (HCMV) is highly prevalent in most populations worldwide and has a major influence on shaping the human immune system. Natural killer (NK) cells are important antiviral effectors that adapt to HCMV infection by expansion of virus-specific effector/memory cells. The impact of HCMV infection on the development of NK cells and innate lymphoid cells (ILC) in general is less well understood. In this context, we have recently established a novel in vitro platform to study human NK cell developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Because mouse and human hILCs differ significantly ( 71 ), study in the human system is critical. Using human hILCs co-cultured with viruses in vitro , hILCs were shown to respond to rhinovirus ( 72 ), IAV ( 56 , 58 ), and human cytomegalovirus (HCMV) ( 73 ). However, the study of hILCs in natural viral infection in humans has been limited to those of HIV infection ( 74 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because mouse and human hILCs differ significantly ( 71 ), study in the human system is critical. Using human hILCs co-cultured with viruses in vitro , hILCs were shown to respond to rhinovirus ( 72 ), IAV ( 56 , 58 ), and human cytomegalovirus (HCMV) ( 73 ). However, the study of hILCs in natural viral infection in humans has been limited to those of HIV infection ( 74 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, Elango, J. et al noted that the parathyroid hormone-related protein (PTHrP) shows accelerated soluble receptor activator of nuclear factor (NF)-kB ligand (sRANKL) downregulation of osteogenesis of MSCs, by increasing RANK expression at the earlier stage of differentiation and by inhibiting ANK [7]. On the other hand, Ising, R. et al successfully differentiated cord blood-derived hematopoietic progenitor into mature CD56+CD94+NKG2A+NK (Natural Killer) cells on HCMV (Human cytomegalovirus)-infected MSCs from bone marrow, with significantly higher anti-viral cytokine production compared to NK cells developing on non-infected MSCs [8]. Behm, C. et al observed that Vitamin D3 increases or decreases the immunomodulatory activities of Periodontal ligament-MSCs, depending qualitatively and quantitatively on the presence of specific tumor necrosis factors TNF-α-, Interleukin IL-1β-, and Interferon IFN-γ inflammatory cytokines [9].…”
mentioning
confidence: 99%
“…The MSCbased niche enabled the highly efficient generation of NK cells including expression of KIRs, which are only scarcely generated on murine feeder cell lines (34). In the course of further studies analyzing the effect of human cytomegalovirus infection on NK cell differentiation in vitro, a NKp44 + CD56 + CD94cell subset with similarity to tissue ILC3s was identified by us (35). In the present study, we now provide compelling evidence that these cells indeed represent bona fide effector IL-22-secreting NKp44 + ILC3s and that they can be efficiently generated from umbilical CB-derived HSPC in a human MSC niche.…”
Section: Introductionmentioning
confidence: 99%